THE SUFI LEGACY OF AZIZIDDIN NASAFI AND ITS STUDY - Narzieyev Zubaydillo Ibodilloyevich Ibodilloyevich (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The following article insights on the the sufi legacy of Aziziddin Nasafi and its study based on his treaties “Kashf-ul haqayiq” and Kitab al-insan ul kamil”. The alternative version is also commented.